From the parks to the streets. Corporal, visual and spatial practices in social protest. Rosario, Argentina, 1996-2002 (Palimpsesto, 2018)
In this paper, the relations among corporal practices, visual imaginations, and public space will beanalyzed through a case study. In the city of Rosario (Argentina), towards mid-1990s, a series of aestheticperformaticpractices and languages emerged on the central bank of the Paraná River. Their existencecoincided in time with a reactivation of social protest in response to neoliberal policies applied inArgentina in that period. The artistic knowledge forged in the riparian public spaces appeared on thestreets during the most critical moments of social conflict, endowing the “traditional” forms of protestwith an expressive, playful, and parodic potential. These relationships are here reconstructed mainlythrough personal interview and some documentary materials of the period.
Keywords: City; public space; aesthetic-performatic practices; languages; social protest